Comparative MLVA-Analysis of Vibrio cholerae Strains of Classical Biovar, Isolated in the Russian Federation and Abroad - N. B. Cheldyshova; A. A. Kritsky; Yu. V. Lozovsky; N. P. Guseva (Проблемы особо опасных инфекций, 2016)
Objective of the study is to determine phylogenetic affinity of the Vibrio cholerae strains of classical biovar, isolated between 1937 and 1969 in Russia, to the strains from near and far abroad countries. Materials and methods. Utilized were 27 Vibrio cholerae strains of classical biovar. PCR was carried out applying “BIS M112” amplifier. Genetic analyzer ABI 3500xl was used for sequencing of the strains. MLVA-analysis was performed by reference to 5 MLVA-loci: VC0147, VC0436-0437, VC1650, VCA0171, and VCA0238. Nutrient requirement and soluble hemagglutinin/protease production was established using plate method. Results and conclusions. Identified have been 8 MLVA-clusters and 21 MLVA-types. It is determined that the strains, isolated during atypical cholera outbreak 1942–1943 in Russia, are inhomogeneous as regards phenotype and genotype and fall into two separate groups, one of which is related to the strain, isolated during cholera outbreak 1938 in Khabarovsk, and another group – to the strains from India and China, isolated in 1946 and 1949, respectively.